2009
DOI: 10.1088/0022-3727/42/5/055206
|View full text |Cite
|
Sign up to set email alerts
|

Recombination of chlorine atoms on plasma-conditioned stainless steel surfaces in the presence of adsorbed Cl2

Abstract: We investigated the interactions of atomic and molecular chlorine with plasma-conditioned stainless steel surfaces through both experiments and modelling. The recombination of Cl during adsorption and desorption of Cl2 was characterized using a rotating-substrate technique in which portions of the cylindrical substrate surface are periodically exposed to an inductively coupled chlorine plasma and then to an Auger electron spectrometer in separate, differentially pumped chambers. After several hours of exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…It is also measured by Guha et al [5], and lower values are reported that also depend on the n Cl /n Cl 2 density ratio. Additionally, such a dependence is also observed for a stainless steel wall by Stafford et al [8]. We define these variable recombination probabilities by parametric fits [19] log 10 (γ A2 ) = −0.82 − 1.59 exp −1.81 n Cl n Cl 2 ,…”
Section: Chemical Modelmentioning
confidence: 61%
See 1 more Smart Citation
“…It is also measured by Guha et al [5], and lower values are reported that also depend on the n Cl /n Cl 2 density ratio. Additionally, such a dependence is also observed for a stainless steel wall by Stafford et al [8]. We define these variable recombination probabilities by parametric fits [19] log 10 (γ A2 ) = −0.82 − 1.59 exp −1.81 n Cl n Cl 2 ,…”
Section: Chemical Modelmentioning
confidence: 61%
“…This process has a major effect on the atomic and molecular chlorine densities in the plasma. This recombination rate has been measured by several groups, which have shown that it can depend on numerous parameters such as the atomic to molecular chlorine density ratio [5], the gas temperature [6], the pressure [7], the wall material [6,8], and even the surface coating history [9]. The role of the recombination probability has been studied via models by Lee et al [10] and is further discussed by Meeks et al [11] with experimental comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…At all substrate rotation frequencies, the pressure rises are higher for SS than for AA; we will come back on this point later on. One should note that when the substrate was spun with the plasma off, no increase was observed with rpm for both AA and SS substrates [28,34]. This indicates that, in our experimental conditions, O 2 (unlike Cl 2 ) [31,34] does not stick to the surface and therefore does not participate in the recombination reaction.…”
Section: Determination Of Recombination Coefficients Using the Spinnimentioning
confidence: 70%
“…A "spinning-wall" technique was recently developed for studying surface reactions on plasma reactor walls [28][29][30][31][32][33][34][35][36][37]. This method couples the established ultra-high-vacuum techniques of desorption MS and AES to the high-pressure, high-charge-density plasma environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation